The role of antiparasitc drugs and steroids in Covid-19 treatment (Research, Society and Development, 2021)
Background: COVID-19 has emerged as a pandemic that spread throughout the world in less than 6 months, leaving hundred thousand deaths behind. Surprisingly, old drug arsenal has now been applied as an option of treatment. Objective: The aim of this article was to accomplish a literature review concerning the antiparasitic chloroquine, ivermectin, nitazoxanide; as well as glucocorticoids as possible therapeutic agents to be applied in patients with COVID-19 in Brazilian hospitals. Methodology: clinical evidence of COVID-infected patients and literature consultation have been used for the construction of this article. On line searches and gray literature have also been consulted, whose database include PUBMED Central, BVS/BIREME, Web of Science, Science Direct, Higher Level Personnel Improvement Coordinator (CAPES), Periodic Door (Portal de Periódicos da CAPES, The Cochrane Library and PROSPERO). Results: chloroquine, ivermectin and nitazoxanide present antiviral characteristics to support their usage in phase 1 of COVID-19 symptoms. Glucocorticoids such as methylprednisolone and dexamethasone seem to be more efficient in patients with pulmonary symptoms such as those in phase 2B and 3. Conclusion: According to the articles raised in this review, antiparasitic agents are promising for patients with COVID-19 in the very beginning of the symptoms. Methylprednisolone and dexamethasone are best indicated for hospitalized patients with pulmonary commitment.